2013
DOI: 10.1093/ndt/gft362
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization from transfusion in patients awaiting primary kidney transplant

Abstract: Among prospective primary kidney transplant recipients, RBC transfusion results in clinically significant increases in HLA antibody strength and breadth, which adversely affect the opportunity for future transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 36 publications
2
51
0
2
Order By: Relevance
“…This result is in keeping with a previous study suggesting that blood transfusions in CKD are associated with a 28% decrease in the odds of transplant [18]. Our finding may reflect elevations in panel reactive antibody levels in pretransplant patients who receive blood transfusions [19,20], although we cannot exclude the possibility that it simply reflects a better underlying clinical profile for patients who do not receive transfusions.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in keeping with a previous study suggesting that blood transfusions in CKD are associated with a 28% decrease in the odds of transplant [18]. Our finding may reflect elevations in panel reactive antibody levels in pretransplant patients who receive blood transfusions [19,20], although we cannot exclude the possibility that it simply reflects a better underlying clinical profile for patients who do not receive transfusions.…”
Section: Discussionsupporting
confidence: 92%
“…It is very unlikely that undocumented pregnancy‐induced alloimmunization affected our results as most females studied were premenarchal, older patient age was not associated with alloimmunization and males actually had a higher prevalence of HLA antibodies. Our findings add to the growing body of evidence that HLA alloimmunization after RBC transfusion remains a problem despite leucocyte reduction (Balasubramaniam et al , ; Yabu et al , ). The source of the HLA class I antigens in RBC units causing sensitization is currently unknown.…”
Section: Discussionsupporting
confidence: 75%
“…This has important implications. Recent evidence has shown that RBC transfusion can cause allosensitization [23,24] , such that the increased use of transfusions could possibly result in increased sensitization in the dialysis population overall [23,25,26] . This is important because sensitized kidney transplant candidates wait longer and their graft survival is shorter should they undergo transplant [27] .…”
Section: Discussionmentioning
confidence: 99%